Klasifikasi Metode dan Pendekatan Syarah Hadis dalam Kitab-Kitab Hadis Ahkam (Studi Kitab Bulughul Maram, Subulussalam, Misbahuz Dzolam, dan Nailul Authar) - Dini Astriani (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2021)
This article will discuss the Hadith of the Ahkam Bulughul Maram. In addition to studying the main book of Bulughul Maram, the author will examine several sharia books from Bulughul Maram, namely Subulussalam fi Syarhi Bulguhul Maram, Misbahuz Dzolam fi Syarhi Bulughul Maram, and the book Bustanul Akhbar Mukhtasar Nailul Authar the sharia book from Al Muntaqa Al Akhbar. The author's interest in this study is the aspect of the method and style applied by all authors in writing these books. As for the analysis of the data, the author uses an explanation of the theory of syarah hadith. So by using this theory, in the hypothesis the authors of these books all use the thematic model (maudui) in the field of ahkam (fiqhiyah). While in his syarah, he uses the Tahlili and Muqarran syarah methods. With dominant sharia characteristics in linguistic and fiqhiyah (Shari'a/law) aspects. Bulughul Maram is one of the thematic books of hadith which is included in the thematic category of fiqhiyah, namely thematic books that contain various kinds of hadith ahkam (shari'a amali). The ahkam hadiths themselves are traditions that contain practical legal materials (fiqh amali) of a mukallaf. The fame of Bulughul Maram had an impact on several scholars who tried to steal the book, including Subullussalam fi Syarhi Bulughul Maram by As Shan'ani and Misbahuz Dzolam by KH Muhajirin. In addition, there is also a famous syarah book by As Syaukani with the title Bustanul Akhbar Mukhtasar Nailul Authar, a syarah from the book Al Muntaqa Al Akhbar.